MINI REVIEW: PERBANDINGAN AKTIVITAS ANTIOKSIDAN BEBERAPA SPESIES DAUN SIRIH (Piper sp.) DAN POTENSINYA SEBAGAI TABIR SURYA - Ningrum, Tika Setia; Purba, Ritson; Pasaribu, Subur P. (PROSIDING SEMINAR KIMIA, 2024)
The betel plant (Piper sp.) is a vine that is often used as a medicine or traditional potion. The part that is generally used as medicine is the leaves. Betel leaves can be used as an antiseptic, anti-dyslipid agent, anti-fungal, anti-inflammatory, anti-bacterial and antioxidant. The antioxidants in betel leaves can be used as sunscreen because they can reduce free radicals from exposure to sunlight. Antioxidant activity was tested using the DPPH (2,2 diphenyl-1-picryhydrazyl) method. In this article, a review of the antioxidant activity of various species of betel leaves is carried out, such as green betel leaves (Piper bettle), forest betel (Piper aduncum), Chinese betel (Pepperomia pellucida), yellow betel (Piper betle), and black betel (Piper acre). The results of the literature study show that the highest IC50 value is found in forest betel leaves (Piper aduncum) at 47.252 ppm and the lowest in black betel leaves (Piper acre) at 10.41 ppm. Based on that, the betel leaf that has the best antioxidant activity and potential as a sunscreen is black betel leaf (Piper acre). Keywords: Antioxidants, Betel Leaves, Sunscreen